Mrs.Beeton's Best of British Home Cooking - Mrs. Beeton's (London, United Kingdom Orion Publishing Co, 1998)
Hearty, traditional breakfasts. Delicious roast beef and Yorkshire Pudding. Teacakes and tasty trifles. The aromas of these satisfying dishes make mouths water throughout British households, and you can easily prepare them in your own kitchen. Whip up a mulligatawny soup, or turn a meager amount of meat into a full meal with a "hodge-podge" of beef, onions, carrots, turnips, and spinach. Just a nip of mustard and port transforms boring grilled cheese into a savory Scotch Rarebit. And so much more! Bonus: shortcuts for busy cooks, serving hints, and details on food traditions, festivals, and regional specialties.